Excellent Energy Storage Performance in Bi(Fe0.93Mn0.05Ti0.02)O3 Modified CaBi4Ti4O15 Thin Film by Adjusting Annealing Temperature - Tong Liu; Wenwen Wang; Jin Qian; Qiqi Li; Mengjia Fan; Changhong Yang; Shifeng Huang; Lingchao Lu (Nanomaterials, 2022)
Dielectric capacitors with ultrahigh power density are highly desired in modern electrical and electronic systems. However, their comprehensive performances still need to be further improved for application, such as recoverable energy storage density, efficiency and temperature stability. In this work, new lead-free bismuth layer-structured ferroelectric thin films of CaBi4Ti4O15-Bi(Fe0.93Mn0.05Ti0.02)O3 (CBTi-BFO) were prepared via chemical solution deposition. The CBTi-BFO film has a small crystallization temperature window and exhibits a polycrystalline bismuth layered structure with no secondary phases at annealing temperatures of 500–550 °C. The effects of annealing temperature on the energy storage performances of a series of thin films were investigated. The lower the annealing temperature of CBTi-BFO, the smaller the carrier concentration and the fewer defects, resulting in a higher intrinsic breakdown field strength of the corresponding film. Especially, the CBTi-BFO film annealed at 500 °C shows a high recoverable energy density of 82.8 J·cm−3 and efficiency of 78.3%, which can be attributed to the very slim hysteresis loop and a relatively high electric breakdown strength. Meanwhile, the optimized CBTi-BFO film capacitor exhibits superior fatigue endurance after 107 charge–discharge cycles, a preeminent thermal stability up to 200 °C, and an outstanding frequency stability in the range of 500 Hz–20 kHz. All these excellent performances indicate that the CBTi-BFO film can be used in high energy density storage applications.